Multiple Organ Failure Associated with SARS-CoV-2 Infection in a Child with Down Syndrome: Is Trisomy 21 Associated with an Unfavourable Clinical Course? - Perla Idalia Vazquez-Hernández; Alan Cárdenas-Conejo; Manuel Alejandro Catalán-Ruiz; Karla Navar-Gallegos; Emilio Zenteno-Salazar; Jose Rafael-; Ranferi Aragon-Nogales; Maribel Ibarra-Sarlat; Juan Carlos Núñez-Enríquez (Hindawi Limited, 2021)
Introduction. Down syndrome (DS) is one of the most frequent genomic disorders around the globe (∼1:700 births). During the COVID-19 pandemic, it has been recognized that children with DS are patients with a greater risk of presenting SARS-CoV-2 infection-related poor outcomes. Nonetheless, a few cases with DS and SARS-CoV-2 infection have been reported. Our aim is to describe the unfavorable clinical course of a child with DS infected with SARS-CoV-2 virus. Case. Female, 2 years old, karyotype 47,XX,+21[30], previously diagnosed with a cyanotic congenital heart disease (tricuspid atresia and infundibular pulmonary stenosis, type Ib) who started with diarrhea, developed shortness of breath, and cyanosis and was admitted to the hospital presenting low-oxygen saturation (33%) requiring invasive mechanical ventilation support. The patient tested positive for SARS-CoV-2 infection. During hospitalization, the patient presented hypotension, anuria, retarded capillary filling, and metabolic acidosis; management with vasoactive drugs was needed. Nonetheless, the patient developed respiratory and cardiac failure, acute renal injury (AKIN-III), and septic shock. After 24 days of hospitalization, the patient died. Conclusions. Multiple organ failure observed in the patient presented could be related to the triple gene dose of four interferon receptors (IFNAR1, IFNAR2, IFNGR2, and IL10RB) located at 21q22.11. Additionally, overexpression of TMPRSS2 at the pulmonary level, located also at 21q22.3, could be related with an increased susceptibility for the development of SARS-CoV-2 infection in DS patients.